PERALIHAN (KONVERSI) SPUTUM BTA ANTARA PEMBERIAN DOSIS BAKU (STANDAR) DAN TINGGI RIFAMPICIN PADA PENGOBATAN (TERAPI) ANTI TUBERKULOSIS KELOMPOK (KATEGORI) I - Yani Triyani; Ida Parwati; I. Sjahid; J. E. Gunawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Acid fast bacilli (AFB) sputum microscopy is used as a diagnostic tool of pulmonary tuberculosis (TB) in TB eradication program with directly observed treatment short course (DOTS) strategy. The AFB sputum microscopy should be performed before treatment,two months after intensive phase and four months after advance phase treatment. This study is a part of a research to compare thestandard (450 mg) and high (600 mg) rifampicin dose in patients with pulmonary tuberculosis in Indonesia. The aim of this studywas to detect the sputum conversion time of AFB in pulmonary TB patients who obtained category I antituberculous treatment with standard dose compared to one who received high dose of rifampicin at the beginning and at the end of the intensive phase. This AFB sputum microscopy have been performed from September 2003 until August 2005 from 85 pulmonary TB patients every two weeksusing Ziehl Neelsen and read by means of International Union Against Tuberculosis and Lung Diseases (IUATLD) scale, in PoliklinikParu Balai Pengobatan Penyakit Paru-paru and Department of Internal Medicine RS. Dr. Hasan Sadikin. Patients with pulmonary TBwho obtained category I antituberculous treatment of the intensive phase were divided randomly double blind into two groups, usingstatistical analysis by Page test for order alternative and Mann Whitney test. After randomization, there were 52 patients who receivedstandard dose and 33 patients who had high dose of rifampicin. Sputum conversions of AFB on week 2, 4, 6, and 8 were 36.1%, 63.9%,75%, and 91.7% for standard dose group. Sputum conversions of AFB on week 2, 4, 6, and 8 were 46.2%, 80.8%, 80.8%, and 84.6%for high dose group. Sputum conversion of AFB for high dose group were faster than standard dose group (p=0.030). Dropout (DO)patients were 5.9% (5/85) and no sputum conversion of AFB on week 8 was 8.3% and 15.4% for standard dose group and high dosegroup of rifampicin, respectively. Sputum conversions of AFB for high dose group were found significant more quickly than standarddose group of rifampicin statistically.